When Do Municipal Consolidations Reduce Government Expenditures? Evidence on the Role of Local Involvement. (25th February 2019) - Mughan, Siân
Abstract: Higher levels of government motivate municipal consolidations as a tool to increase efficiency in the local government sector, yet research shows that consolidations typically fail to deliver the promised spending reductions. Since mergers often require significant changes to institutional structures, one explanation is that local decision makers can substantially influence the outcomes of the consolidation process. To explore this possibility, this article contrasts "encouraged but voluntary" mergers with those that were "forced" on local governments in the state of New South Wales, Australia. Results show that voluntary mergers resulted in a 10 percent decline in total per capita expenditures, but forced consolidations failed to reduce spending across the board. The policy conclusion is that decision makers considering structural reform should invest in obtaining the support and participation of local government decision makers .